PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA KOMPETENSI KEAHLIAN APHP DI SMKN 1 MEJAYAN - Rianaya, Adelia Loli; mukti, ebtafil; Yayuk, Erna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The appropriate learning model at the Vocational Education level can have a significant impact on students, particularly in their readiness to face the workforce. This research aims to develop an entrepreneurship-based learning model for normative-adaptive subjects in vocational schools using the Research and Development (R&D) approach of the Four-D model (Define, Design, Develop, Disseminate). The study was conducted at SMKN 1 Mejayan in April-May 2025 with subjects consisting of 30 students and 1 Cultural Arts teacher from the Agribusiness of Agricultural Product Processing (APHP) major. Data were collected through observation, questionnaires, interviews, and documentation, and were then analyzed descriptively both quantitatively and qualitatively. The research results show that the developed model syntax has proven to increase student engagement by 83% and entrepreneurial inspiration by 89%. The integration of entrepreneurial content into the learning of Fine Arts (batik) and English (book composition) successfully eroded students' mental blocks against 'difficult' subjects.